2017
DOI: 10.1371/journal.pgen.1006530
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Post-transcriptional Mechanisms Limit Heading Date 1 (Hd1) Function to Adapt Rice to High Latitudes

Abstract: Rice flowering is controlled by changes in the photoperiod that promote the transition to the reproductive phase as days become shorter. Natural genetic variation for flowering time has been largely documented and has been instrumental to define the genetics of the photoperiodic pathway, as well as providing valuable material for artificial selection of varieties better adapted to local environments. We mined genetic variation in a collection of rice varieties highly adapted to European regions and isolated di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 71 publications
5
96
0
Order By: Relevance
“…This observation suggests the existence of a mechanism that downregulates their expression upon commitment to flowering and that could possibly depend on Ehd1, encoding a common upstream promoter of Hd3a and RFT1 expression (Goretti et al, 2017;Ogiso-Tanaka et al, 2013;Gómez-Ariza et al, 2015). Under our growing conditions, expression of the florigens reached a peak ;12 to 15 d after shifting plants from LD to SD (Galbiati et al, 2016).…”
Section: A Negative Feedback Loop Independent Of Osfd1 Limits Florigementioning
confidence: 64%
“…This observation suggests the existence of a mechanism that downregulates their expression upon commitment to flowering and that could possibly depend on Ehd1, encoding a common upstream promoter of Hd3a and RFT1 expression (Goretti et al, 2017;Ogiso-Tanaka et al, 2013;Gómez-Ariza et al, 2015). Under our growing conditions, expression of the florigens reached a peak ;12 to 15 d after shifting plants from LD to SD (Galbiati et al, 2016).…”
Section: A Negative Feedback Loop Independent Of Osfd1 Limits Florigementioning
confidence: 64%
“…Our data (Figures 5 and 6) suggest that the CCT does contact the same acidic surface patch of the HFD dimer recognized by NF-YA A1. A variant in this basic CCT region of both Heading date 1 (Hd1; the rice CO homolog) and OsPRR37 (another rice CCT protein involved in flowering) also impairs HFD interactions (Goretti et al, 2017), further solidifying the idea that multiple CCTs can form NF-CO complexes.…”
Section: Nf-co and Nf-y In Floweringmentioning
confidence: 96%
“…Specifically, there is well established evidence that different NF-Y HFD subunits are involved in the regulation of timing of flowering in Arabidopsis (Wenkel et al, 2006;Chen et al, 2007;Cai et al, 2007;Kumimoto et al, 2008Kumimoto et al, , 2010Hackenberg et al, 2012;Hou et al, 2014;Cao et al, 2014), rice (Oryza sativa; Dai et al, 2012;Wei et al, 2010;Yan et al, 2011;Feng et al, 2014;Chen et al, 2014;Kim et al, 2016;Hwang et al, 2016;Goretti et al, 2017), wheat (Triticum aestivum; , and tomato (Solanum lycopersicum; Ben-Naim et al, 2006). Wenkel et al originally observed homology between the CCT domain and the conserved domain of NF-YA, suggesting that CO and NF-YA might both bind DNA with NF-YB/NF-YC HFD dimers (Wenkel et al, 2006).…”
Section: Nf-co and Nf-y In Floweringmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice (Oryza sativa) is a typical SD plant whose flowering is promoted under SD conditions, but delayed under LD conditions (Yano et al, 2000). During rice domestication and genetic breeding, rice has dramatically expanded its cultivating areas through modulation of the flowering regulatory pathways (Goretti et al, 2017;Itoh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%